The Interplay Between the Notch Signaling Pathway and Cellular Metabolism - Slaninová, Věra (Jihočeská univerzita, 2017)
We identified four metabolic genes as direct targets of Notch signaling pathway both in vitro and in vivo and investigated the hypothesis that Notch directed metabolic changes support the growth of the imaginal wing dics. Vice versa, we observed the influence of metabolic changes on the activity of Notch signaling pathway and we identified Sirt1 as a metabolic sensor for the Notch pathway that helps to elicit an efficient response to Notch signal, in a metabolism sensitive manner.
The Interplay Between the Notch Signaling Pathway and Cellular Metabolism
Keywords: Notch; metabolism; growth; metabolic sensors; sirt1; Notch; metabolism; growth; metabolic sensors; sirt1